Religious culture as a factor of the formation of ethnic identity of Ukrainians in the context of Ivan Ohienko’s creative heritage - Zainchkivska, Iryna (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2019)
The article analyzes the ideological intentions of Ohienko and it shows that the works of the thinker were aimed at revealing the factors which, on the one hand, ensured the emergence of a distinctive Ukrainian ethno-cultural space, on the other hand, they could have great importance in the process of confronting the assimilation policy of the neighboring countries, and therefore should be taken into account in the process of developing modern strategies of national consolidation. It is proved that term “Ukrainian Church” widely used by Ohienko in various works, does not exhaust the entire diversity of the studied phenomenon, but simultaneously has caused contradictions regarding interpretation of a number of substantiated scholarly positions. It is shown that using the term “Ukrainian Church”, the scientist researched religious culture, that is, a system of religious and worldview ideas that defines the whole sphere of life and values of pre-industrial society